Monitoring on-farm water storage use: from LIDAR to multi-source remote sensing - Chemin, Yann H.; Rabbani, U. (2011)
Faced with unreliable rainfall patterns, Australian farmers have developed on-farm water storage (OFS) solutions over the drought years. Recent thinking in water policy under the Commonwealth government considers extending the Cap over surface water to OFS as they are not currently covered under the Cap and eluded the effective water policy arrangements across users and the states. A unified approach to Cap implementation involving water diversions from the river system, OFS and other direct diversions and withdrawals as well as groundwater extractions is essential to enhance the scope and integrity of the Cap mechanism and bring diversions within the sustainable yield limits. This study lays ground for a detailed volume assessment calibration of each OFS within a water basin, within the prospect of using such information to enable a multi-source remote sensing monitoring system.